The Marcos Human Rights Victims the struggle for Justice and Reparations, 1986-1999 - Mendoza, Meynardo P. (Quezon City Department of Philosophy, College of Social Sciences and Philosophy, University of the Philippines Diliman, 2010)
Twenty four years after the downfall of the Marcos regime, the dark legacies of the martial law era remain unresolved. One of these is the plight of thousands of human rights victims who suffered illegal detention, torture and even summary executions. Known collectively as the Marcos human rights victims, they still await justice and closure from the Philippine government. Although they won a landmark case against the Marcos Estate in a Hawaii court in 1992 that convicted the former dictator for gross human rights violations and levied on the heirs almost
"Summer 2010."
Thesis (Ph.D. Philosophy)--University of the Philippines Diliman.
Keywords: Political crimes and offenses -- Philippines; Reparations for historical injustices -- Philippines